Apparent mineralocorticoid excess caused by novel compound heterozygous mutations in HSD11B2. (25th November 2020) - Fan, P; Zhang, D; Yang, K.Q; Zhang, Y; Lu, Y.T; Luo, F; Tian, T; Liu, Y.X; Zhou, X.L
Abstract: Background: Apparent mineralocorticoid excess (AME) is a rare autosomal recessive genetic disorder caused by a mutation in the 11β-hydroxysteroid dehydrogenase type 2 gene (HSD11B2). AME is characterized by early-onset and severe hypertension, hypokalemia, and metabolic alkalosis. Purpose: This study aimed to study the molecular genetics, clinical presentation, biochemical parameters, and treatment in the proband with AME from a non-consanguineous Chinese family. Methods: Genomic DNA was recovered from peripheral blood leukocytes from nine subjects in this family. Next-generation sequencing and Sanger sequencing were performed to identify the HSD11B2 variants. In silico and genotype-phenotype correlations analyses were used to predict pathogenicity of candidate variants. A tailored therapy was performed for identified mutations carriers. Results: Genetic analysis identified novel compound heterozygous HSD11B2 mutations (c.343-348del/c.1099-1101del) in the proband. In silico analysis predicted these HSD11B2 mutations were deleterious. The structural change and predicted consequences owing to the compound mutations have been modeled. The same compound mutations were not found in any other family members, 100 hypertensives, or 100 healthy controls. The proband had typical manifestations of AME, including early-onset and severe hypertension, hypokalemia, low plasma aldosterone concentration, hypokalemic alkalosis and nephrolithiasis. The probands' blood pressure and serum potassium level had returned to normal after treatmennt with dexamethasone (1.5 mg/day) and spirolactone (40 mg/day) for three months. Conclusions: We conclude that this novel compound mutations are responsible for AME in the proband. These genetic and clinical data expand the genetic spectrum of HSD11B2 and demonstrate the pathogenic effects of identified mutations and genotype-phenotype correlations. It is emphasized that genetic diagnosis and specific treatment play an important role in patients with AME. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Key Research and Development Program of China; PUMC Youth Fund and the Fundamental Research Funds for the Central Universities